2023
DOI: 10.3389/fmed.2023.1135063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance and balance exercises for athletic ability and quality of life in people with osteoporotic vertebral fracture: Systematic review and meta-analysis of randomized control trials

Abstract: PurposeThis study aimed to use meta-analysis to determine the impact of resistance and balance training on athletic ability and quality of life for patients with osteoporotic vertebral fracture (OVF).MethodsThis study followed the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) criteria for systematic reviews and meta-analyzes. The PubMed, Web of science, Cochrane, Embase, and CNKI databases were searched for randomized controlled trials (RCTs) up to September 2022. The search strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Studies were included if they: (1) were published in English, peer-reviewed, and full-text accessible; (2) clinically evaluated improvement of balance and/or gait performance; (3) provided telerehabilitation or in-home balance and/or gait exercises; (4) used smartphone-or tablet-based technology with or without additional sensors for telerehabilitation or in-home use; (5) had experimental protocols for more than four weeks based on the recommended period for gait and gait rehabilitation [30][31][32][33][34]; and (6) had participants with balance and/or gait impairments caused by age, diseases, or clinical conditions.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were included if they: (1) were published in English, peer-reviewed, and full-text accessible; (2) clinically evaluated improvement of balance and/or gait performance; (3) provided telerehabilitation or in-home balance and/or gait exercises; (4) used smartphone-or tablet-based technology with or without additional sensors for telerehabilitation or in-home use; (5) had experimental protocols for more than four weeks based on the recommended period for gait and gait rehabilitation [30][31][32][33][34]; and (6) had participants with balance and/or gait impairments caused by age, diseases, or clinical conditions.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…A few review articles have documented recent efforts to build smartphone-based telerehabilitation technology to improve balance and gait performance, which typically covers design, development, and preliminary assessment in a laboratory setting [27][28][29]. However, these review articles have not examined the effects of long-term use of smartphone-based telerehabilitation, although multiple review articles have suggested balance and gait exercises for at least four weeks to improve performance in various populations (e.g., older adults and individuals with musculoskeletal injuries and neurological disorders) [30][31][32][33][34]. Furthermore, no systematic review has examined sustained improvement, performance retention, and potential carry-over effects of long-term smartphone-or tablet-based balance and gait telerehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews and meta-analyses have demonstrated the positive impact of exercise modalities, as non-pharmacological approaches, on bone density in postmenopausal women. Exercises play a crucial role in reducing bone density loss by maintaining both cortical and trabecular bone density [ 5 ]. Specifically, balance exercises, by stimulating proprioceptive receptors and enhancing reaction times, are pivotal in preventing falls [ 3 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, balance exercises, by stimulating proprioceptive receptors and enhancing reaction times, are pivotal in preventing falls [ 3 , 6 , 7 ]. Physical exercise proves to be a cost-effective approach, providing favourable effects on fall risk and bone strength without significant adverse effects [ 5 ].…”
Section: Introductionmentioning
confidence: 99%